(untitled) (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
C-reactive protein (CRP) is a sensitive biomarker of systemic inflammation. Elevated CRP has been implicated in vascular endothelial dysfunction, metabolic derangement, and atherothrombotic disease. Its prognostic significance in acute ischemic stroke (AIS) remains an area of clinical relevance. Despite the known associations between CRP levels and cerebrovascular outcomes, AIS remains underexplored in South Indian populations, where metabolic comorbidities are highly prevalent. Objectives: To evaluate the association between admission CRP levels and clinical outcomes in AIS and to examine correlations between CRP, blood pressure, and blood glucose. Methods: A prospective observational study was conducted on 100 radiologically confirmed AIS patients at Government Thiruvarur Medical College. Admission CRP, systolic and diastolic blood pressure (SBP, DBP), and blood glucose were recorded. Correlations were analyzed using Pearson’s test, with p < 0.05 considered statistically significant. Results: Mean CRP was 18.12 ± 17.79 mg/L, SBP 146.40 ± 38.07 mmHg, DBP 89.50 ± 18.27 mmHg, and glucose 229.88 ± 122.78 mg/dL. Elevated CRP (>6 mg/L) was observed in 89% of patients. CRP correlated negatively with SBP (r = –0.214, p = 0.032) and DBP (r = –0.261, p = 0.009), while correlation with glucose was weak and non-significant (r = 0.044, p = 0.662). Patients with CRP >10 mg/L had a 41.6% mortality rate versus 9.1% in those with normal CRP levels. Conclusion: Elevated admission CRP is significantly associated with poor outcomes in AIS. Its significant inverse correlation with blood pressure suggests a hemodynamic–inflammatory interplay that may reflect vascular dysregulation in severe strokes. Integrating CRP testing into early stroke assessment could improve prognostication and guide anti-inflammatory or hemodynamic-targeted therapies